Experimental and numerical modelling of desiccation shrinkage process of kaolin clays - Wenqing Cheng; Hanbing Bian; Hao Shi; Fangfang Xun (Scientific Reports)
Abstract With global climate change, extreme weather occurs more and more frequently, leading to soil cracking becoming a common disaster. The desiccation cracks of soils can have a serious impact on the soils performance. Considering the initially saturated unconsolidated clayey soils, it may undergo shrinkage deformation due to water loss during the drying process, which is limited by various boundary conditions and represents one of the fundamental reasons for drying cracking. Nevertheless, identifying the stress of clay soil slurry with different water content is quite challenging in both experimental and numerical approaches. Presently, a combined numerical simulation and experiments research was conducted to investigate the constrained drying process of remolded clayey soil, using the strain analysis to reveal the drying shrinkage process. The strain process is divided in two parts: the free shrinkage deformation caused by water loss, and the mechanical strain generated by restricted boundary condition. The measurements of soil physical parameters variations during desiccation tests were carried out using Digital Image Correlation method, while numerical simulations helped to estimate the variable fields and enhanced significantly the understanding of experimental results. Finally, the desiccation shrinkage process of clay was successfully reproduced through simulation and an accurate evolution and distribution of tensile strain field was obtained through simulation.